'We are not as they think about us': exploring Omani EFL learners' 'selves' in digital social spaces. (3rd July 2017) - Little, Sabine; Al Wahaibi, Suad
Abstract: This paper reports a research study of Omani EFL learners' motivation to engage in social technologies through the medium of English, adopting Dörnyei's L2 Motivational Self System as the main theoretical framework, whilst exploring other emergent context-sensitive motivational driving forces. The purpose of the research study was to explore identities and self-perceptions of Omani nationals using social media to learn English, an under-researched context. Reflective focused group discussions were conducted with 14 university-age students, along with individually composed language learning histories. The data of the research lend substantial support to the relevance of the L2 Motivational Self System in the Omani context, highlighting, in particular, the emerging collective national and religious identities of young Omani nationals. The paper argues for the need to deepen and broaden our understanding of the association of English social technologies and the national and religious affiliations of learners.